Reducing carotenoid loss during storage by co-encapsulation of pequi and buriti oils in oil-in-water emulsions followed by freeze-drying: Use of heated and unheated whey protein isolates as emulsifiers. (April 2020) - Comunian, Talita Aline; Silva, Marluci P.; Moraes, Izabel Cristina Freitas; Favaro-Trindade, Carmen S.
Graphical abstract: Highlights: Emulsions with heated WPI exhibited better behavior in terms of instability index. Heated and unheated WPI enhanced the protection of total carotenoids. Encapsulation of pequi and buriti oils improved their oxidative stability. Abstract: Buriti and pequi oils are rich in carotenoids and beneficial to human health; however, carotenoid oxidation during storage causes color loss in foods, making it difficult to use these oils in food products. This research aimed to encapsulate pequi oil and co-encapsulate pequi and buriti oils by emulsification using whey protein isolate (WPI) as an emulsifier in two forms, natural (unheated) and heated, followed by freeze-drying. The emulsions were studied by droplet size under different stress conditions, instability index, and rheology. The freeze-dried (FD) samples were studied after accelerated oxidation and the total carotenoid retention was determined; for the reconstituted FD, the zeta potential and droplet size were recorded after storage at 37 °C for 30 days. The emulsions were stable in all conditions, with average droplet sizes between 0.88 ± 0.03 and 2.33 ± 0.02 μm, and formulations with heated WPI presented the lowest instability index values. The FD's zeta potential values ranged from −50 ± 3 to –32 ± 3 mV. The co-encapsulated oils presented higher carotenoid retention (50 ± 1 and 48 ± 1%) than the free oils (31 ± 2%) after 30 days. The oxidative stability indexes were 51 ± 4 and 46 ± 3 for the co-encapsulated oils with unheated and heated WPI, respectively, and 20.5 ± 0.1 h for the free oils. FD formulations with 1:3 ratio of oil: aqueous phase and heated or unheated WPI showed the best carotenoid retention and oxidative stability, indicating that FD oil emulsions have potential as next-generation bioactive compound carriers.